Analysis of the impacts of logistics 4.0 in an agricultural company in the city of Cambé, Paraná State, Brasil (Research, Society and Development, 2020)
This study has as general objective to analyze the impacts generated by logistics 4.0 in an agricultural company located in the State of Paraná.  As for methodological aspects, this is an exploratory research, a single case study, with a qualitative approach to the data. A standardized question script was used for data collection, based on the theoretical framework of the study, with application via e-mail. For data analysis, content and word number analysis were used. It is colluded with the study that logistics 4.0 is an emerging theme and the company in question has been gradually inserting these concepts in its productive area, impacting on financial results.